Los límites de la libertad de expresión en la regulación de redes sociales - Pasquel, Juan C. (2020)
The research work has the general objective of analyzing the limits of freedom of expression inthe regulation of social networks and in the specific objectives of explaining the essential content of the right to freedom of expression, describing the protection mechanism established for the right to freedom of expression and as a last objective to analyze the policies that censure the right tofreedom of expression on social networks. The methodology used will be qualitative, because it corresponds to a diverse range of ways of understanding and knowing the realities that shape human behavior in social networks. It is based on the collection of information, through documents, magazines and statistics to build knowledge have elements in common. The result includes a list of doctrine, norms, and jurisprudence, which may be applicable to the use of socialnetworks. This investigation aims to dilute the censorship exercised against the right to freedom of expression by government authorities. Furthermore, the limitations and legitimate restrictions on freedom of expression, contained in international human rights instruments, such as theAmerican Convention on Human Rights, are concluded. Likewise, this project establishes the general guidelines that will be followed for a regulatory regulation of social networks on the internet, if feasible.